2020
DOI: 10.1038/s41467-020-18461-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol oxidation as alternative anode reactions paired with (photo)electrochemical fuel production reactions

Abstract: (Photo)electrochemical cells that produce fuels have often relied on water oxidation to complete the redox cycle. Here, the authors discuss alcohol oxidation as an alternative reaction and consider general mechanistic features of oxidation electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 19 publications
1
85
0
Order By: Relevance
“…[ 1–3 ] It allows the production of precious chemicals via a more benign, facile, and less expensive route than the traditional routes. [ 4–10 ] Furthermore, water oxidation is often associated with a large overpotential and with catalyst decomposition. [ 11–14 ] In contrast, the oxidation of oxidizable organic molecules usually requires a lower potential, reducing the total hydrogen production cost.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] It allows the production of precious chemicals via a more benign, facile, and less expensive route than the traditional routes. [ 4–10 ] Furthermore, water oxidation is often associated with a large overpotential and with catalyst decomposition. [ 11–14 ] In contrast, the oxidation of oxidizable organic molecules usually requires a lower potential, reducing the total hydrogen production cost.…”
Section: Introductionmentioning
confidence: 99%
“…For Ni and Co two reaction mechanisms were proposed, as illustrated in Figure 8D: i) direct electron transfer in which alcohol molecules adsorb on the M(OH) 2 and get oxidized by the OH − ions trapped on the surface; ii) indirect electron transfer from the reactant to MOOH, restoring the M(OH) 2 . [128][129][130] The works reported by Fleischmann et al in 1970s point toward the indirect reaction pathway. [131,132] At lower glycerol concentration though, Houache et al observed direct electron transfer pathway for Ni.…”
Section: H O H O Oxidation Products H E Anode Reactionmentioning
confidence: 97%
“…[134] Under these conditions, oxidation rate becomes dependent of potential. [128] With the above knowledge at hand, in the following sections we will review in detail for different organic molecules, how the choice of electrocatalysts will affect the reaction activity and selectivity.…”
Section: Intrinsic Metal Properties For Different Chemical Bond Activationmentioning
confidence: 99%
“…[36] Alternatively, a different anodic process could generate a second product in a paired electrochemical process, as in chlor-alkali technology that produces Cl2 and NaOH from brine. [50] Multiple oxidation candidates are available, including biomass, [40,51] various amines, [52] or the production of high value oxidants e.g. HClO and S2O8 2-.…”
Section: Latest Developments For H 2 O 2 Electrosynthesismentioning
confidence: 99%